Impacts of climate change and fruit tree expansion on key hydrological components at different spatial scales - Xu, Yarui; Liu, Wenfei; Fan, Houbao; Shen, Fangfang; Wu, Jianping; Liu, Peng; Sang, Dongxin; Qiu, Wanbin; Duan, Honglang; Cai, Wei (Frontiers in Forests and Global Change, 2023)
Assessing how fruit tree expansion and climate variability affect hydrological components (e.g., water yield, surface runoff, underground runoff, soil water, evapotranspiration, and infiltration) at different spatial scales is crucial for the management and protection of watersheds, ecosystems, and engineering design. The Jiujushui watershed (259.32km2), which experienced drastic forest changes over the past decades, was selected to explore the response mechanisms of hydrological components to fruit tree expansion and climate variability at different spatial scales (whole basin and subbasin scale). Specifically, we set up two change scenarios (average temperature increase of 0.5 °C and fruit tree area expansion of 18.97%) in the SWAT model by analyzing historical data (1961 2011). Results showed that climate change reduced water yield, surface runoff, and underground runoff by 6.75, 0.37, and 5.91 mm, respectively. By contrast, the expansion of fruit trees increased surface runoff and water yield by 2.81 and 4.10 mm, respectively, but decreased underground runoff by 1 mm. Interestingly, the sub-basins showed different intensities and directions of response under climate change and fruit tree expansion scenarios. However, the downstream response was overall more robust than the upstream response. These results suggest that there may be significant differences in the hydrological effects of climate change and fruit tree expansion at different spatial scales, thus any land disturbance measures should be carefully considered.